The influence of a company's communicated CSR initiative on private consumer behavior - Müller, Isabella Iris (2019)
The aim of this research is to determine if and how the communication of a company’s CSR initiative influences private consumer behavior. Hereby it is also considered whether the consumers’ support of the issue at hand exerts influence on private behavior and evaluations of the company behind the CSR initiative. In order to answer the research questions, an online experiment was conducted that was aimed at assessing differences in reported sustainable behavior among participant groups, of which one was exposed to a CSR initiative by a company. The answers to the questionnaire show no significant changes in reported consumer behavior between participant groups. This shows that desirable and specific behavioral outcomes of CSR initiatives are difficult to predict and measure due to the multifaceted nature of CSR. Moreover, CSR seems to entail more advantages for the company rather than consumers or society as a whole. On this basis, the communication of a company’s CSR initiative is recommended to reap known benefits but does not seem to evoke changes in private and unrelated consumer behavior.